(untitled) (Świat Idei i Polityki, 2014)
The article aims to present the controversy among the representatives of the European private sector that has raised because of one of the priorities of the European Commission communication in 2013 — “Directive open, safe and secure cyberspace”. Its legal articles (concerning the need to inform about hacker attacks on private servers) divided opinion on the Old Continent. This paper presents the main assumptions of the document, the analysis of the disputed wording, and forecasts of possible solutions concerning analysis of the so called “cyber-stalemate”.